1980
DOI: 10.1111/j.1365-2125.1980.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trial of labetalol and acebutolol, alone or associated with dihydralazine, in treatment of essential hypertension.

Abstract: 1 Labetalol, an alpha‐ and beta‐ adrenoceptor blocking drug, was compared with acebutolol, alone or associated with dihydralazine in forty patients with moderate essential hypertension. 2 Labetalol (400‐ 800 mg daily) seemed to have a slightly higher potency than acebutolol alone (400–800 mg daily). 3 Labetalol (1200–1600 mg daily) had the same potency as the combination of acebutolol (400–800 mg daily) and dihydralazine (50–100 mg daily). 4 Contrarily to acebutolol, the drop in blood pressure with labetalol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A between-patient study in 40 patients found that labetalol 400-800 mg daily was more effective than acebutolol 400-800 mg daily but the combination of acebutolol 800 mg daily plus dihydrallazine 25 or 50 mg twice daily was similar in effect to labetalol up to 800 mg twice daily. In this study a correlation between the initial renin levels and response to acebutolol was noted but there was no such correlation for the response to labetalol (Thibonnier et al, 1980). Labetalol and methyldopa or sympathetic inhibitory drugs Prichard and Boakes (1976) have reported a longterm study largely with patients already under treatment with existing anti-hypertensive drugs.…”
Section: Labetalol and 0-blockers Plus Hydrallazinementioning
confidence: 58%
See 1 more Smart Citation
“…A between-patient study in 40 patients found that labetalol 400-800 mg daily was more effective than acebutolol 400-800 mg daily but the combination of acebutolol 800 mg daily plus dihydrallazine 25 or 50 mg twice daily was similar in effect to labetalol up to 800 mg twice daily. In this study a correlation between the initial renin levels and response to acebutolol was noted but there was no such correlation for the response to labetalol (Thibonnier et al, 1980). Labetalol and methyldopa or sympathetic inhibitory drugs Prichard and Boakes (1976) have reported a longterm study largely with patients already under treatment with existing anti-hypertensive drugs.…”
Section: Labetalol and 0-blockers Plus Hydrallazinementioning
confidence: 58%
“…In this study a correlation between the initial renin levels and response to acebutolol was noted but there was no such correlation for the response to labetalol (Thibonnier et al, 1980). Labetalol and methyldopa or sympathetic inhibitory drugs Prichard and Boakes (1976) have reported a longterm study largely with patients already under treatment with existing anti-hypertensive drugs.…”
Section: Labetalol and 0-blockers Plus Hydrallazinementioning
confidence: 91%